Empowered Employees, Stronger Banks: Investigating the Nexus between Psychological Empowerment and Job Satisfaction in Nepal - Sharma, Dilli Raj; Mahato, Bijay; Yadav, Ranju (The Mega Journal, 2025)
The research explores the effect of psychological empowerment on the level of employees’ job satisfaction pertaining the strong persuasive impact on the employees working in commercial banks in Nepal. Having employees feeling psychologically empowered plays different roles in shaping employees’ job perceptions and experiences within the organization. Of these, self determination and impact cognition were the strongest. This suggests that employees’ perceptions of autonomy, in conjunction with the autonomy they feel that they possess, coincide with the degree to which they feel the decision-making outcome of the organization regards their input as valuable. The same can be said with respect to confidence and having something to do with workstation competence and meaningful work. Psychological empowerment and job satisfaction correlation and regression analysis highlighted the relevance of psychological empowerment in regard to its framework as a human resource management strategy, particularly within the Nepalese banking sector. The result reinforces motivation theories, particularly in light of focus with the developing nations. In practice, they suggest that banks can improve organizational effectiveness by designing organizational contexts that foster employee independence, skill advancement, role value, and perceived impact. These approaches are crucial to developing a satisfied, motivated, and high performing workforce in today’s competitive and ever-changing financial services market.